2007
DOI: 10.1099/jmm.0.46835-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of bacterial and archaeal species in symptomatic and asymptomatic endodontic infections

Abstract: Phylogenetic analysis of bacterial and archaeal 16S rRNA was used to examine polymicrobial communities within infected root canals of 20 symptomatic and 14 asymptomatic patients. Nucleotide sequences from ∼750 clones amplified from each patient group with universal bacterial primers were matched to the Ribosomal Database Project II database. Phylotypes from 37 genera representing Actinobacteria, Bacteroidetes, Firmicutes, Fusobacteria and Proteobacteria were identified. Results were compared to those obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 36 publications
7
70
1
4
Order By: Relevance
“…The primers 27F-P and 1492R-P are "first-generation" nondegenerate universal bacterial primers that remain in widespread use today (1,5,18,19,39), and 27F-HT and 1492R-HT are more recently published primers that are based on the original first-generation primers and include several degenerate positions to broaden their scope of targets (37). These primers produce nearly full-length 16S rRNA gene sequences and thus provide a fair assessment of the miniprimer method relative to standard methods in common use; duplicate libraries were constructed with each of the primer pairs ( Table 2).…”
Section: Vol 74 2008 Miniprimer Pcr 843mentioning
confidence: 99%
“…The primers 27F-P and 1492R-P are "first-generation" nondegenerate universal bacterial primers that remain in widespread use today (1,5,18,19,39), and 27F-HT and 1492R-HT are more recently published primers that are based on the original first-generation primers and include several degenerate positions to broaden their scope of targets (37). These primers produce nearly full-length 16S rRNA gene sequences and thus provide a fair assessment of the miniprimer method relative to standard methods in common use; duplicate libraries were constructed with each of the primer pairs ( Table 2).…”
Section: Vol 74 2008 Miniprimer Pcr 843mentioning
confidence: 99%
“…16S rDNA sequencing has shown that the infected canals contain a more diverse flora than previously recognized (Vickerman et al, 2007), but surprisingly symptomatic root canal lesions harbor a less diverse flora than do asymptomatic lesions. Certain Streptococcus spp.…”
Section: Endodontic Infectionsmentioning
confidence: 97%
“…Methanobrevibacter oralis-like phylotypes are found in oral niches but their pathological associations are yet to be determined (Lepp et al, 2004;Vickerman et al, 2007) DNA microarrays to study the diversity of subgingival plaque microflora…”
Section: Study Scope Main Findings and Remarks Referencesmentioning
confidence: 99%
“…It can also be detected in root-canal samples. [10] Archaea have been isolated from the human oral cavity, gut, colon, and vagina; [3,9] but have not been established as causes of human disease. [3] It has been detected that interactions between viruses and bacteria within periodontal pockets is as a process of etiopathogenesis of periodontal diseases.…”
Section: Periodontitis As An Infectious Diseasementioning
confidence: 99%